EFFECTIVENESS OF GLYPHOSATE AND 2.4 D AMIN HERBICIDES TO CONTROL WEEDS UNDER Shorea selanica Bl. PLANTATION IN CARITA TRIAL GARDEN, BANTEN - Wibowo, Ari; Nazif, Muhamad (Indonesian Journal of Forestry Research, 2007)
A trial was carried out in Carita, West Java, to identify the effectiveness of Glyphosate and 2.4 D Amin Herbicide to control weeds under Shorea selanica Bl. plantation. The trial was conducted through the application of Glyphosate and 2.4 D Amin Herbicide with dosages of 5, 6, 7, 8 and 9 liter per ha and compared with Glyphosate herbicide 5 liter per ha, manual treatment, and control (no treatment). The result showed that Glyphosate and 2.4 D Amin Herbicide could be used to control weeds in order to maintaining S. selanica Bl. plantation. Minimum dosage of 6 liter/ha was effective to control weeds such as Chromolaena odorata DC, Mikania micrantha Will, Lantana camara L, Imperata cylindrica Beauv., Melastoma malabathricum L, and Boreria latifolia Bl. Furthermore, there was no symptom of poison on S. selanica Bl. plantation after herbicide application with all dosages applied.